Obstetric anal sphincter injury: retrospective review of risk factors - Zakaria , Zahar Azuar (2001)
Objective: To identify the epidemiology and risk factors associated with obstetric anal sphincter injury during vaginal delivery. Methodology: A five years retrospective review of 52 patients who sustained obstetric anal sphincter injury during vaginal delivery in Hospital Universiti Sains Malaysia, Kubang Kerian, Kelantan between January 1996 to December 2000. The control was the three singleton vaginal deliveries prior to and following the index delivery. Logistic regression analysis was used to assess risk factors. Results: There were 52 patients who had obstetric anal sphincter injury after vaginal delivery amongst 32,831 singleton vaginal deliveries at term, giving an incidence of 0.l6%. There was no significant difference in maternal age and gestational age at delivery time. No association was seen in term of past history of instrumental delivery, presentation of the fetus, the use of mediolateral episiotomy, oxytocin augmentation of labour or the use of analgesia (intramuscular Pethidine and epidural analgesia) during labour.